Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.watres.2017.05.055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of advanced secondary municipal wastewater treatment on the molecular composition of dissolved organic matter

Abstract: There is a growing interest in water reuse and in recovery of nutrients from wastewater. Because many advanced treatment processes are designed to remove organic matter, a better understanding of the composition of dissolved organic matter (DOM) in wastewater is needed. To that end, we assessed DOM in the Nine Springs Wastewater Treatment Plant in Madison, Wisconsin by UV–visible spectroscopy and Fourier transform-ion cyclotron resonance mass spectrometry. Samples were collected from the influent and effluent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(120 citation statements)
references
References 46 publications
(99 reference statements)
11
107
2
Order By: Relevance
“…Nominal masses of peaks were determined by adding the mass of a proton and a linear calibration was applied, as described previously. 29 Formulas containing C, H, O, and 13 C were considered for matching. For a formula assignment to be considered successful, the error had to be less than 0.2 ppm and it had to be part of a homologous series with more than three members (CH 4 versus O or ± CH 2 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Nominal masses of peaks were determined by adding the mass of a proton and a linear calibration was applied, as described previously. 29 Formulas containing C, H, O, and 13 C were considered for matching. For a formula assignment to be considered successful, the error had to be less than 0.2 ppm and it had to be part of a homologous series with more than three members (CH 4 versus O or ± CH 2 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…It has been extensively investigated regarding its composition, structure, source, sink and the migration process in the aquatic environments [2,3]. DOM can directly affect nutrient cycling [4], the toxicity of organic pollutants [5], the solubility of heavy metals [6] and the aquatic ecosystem [5,7], and also indirectly influence the atmospheric CO 2 level and global climate change [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that carefully planned potable water reuse projects should be able to provide a level of protection from waterborne illness and chemical contaminants comparable to (and, in some cases, better than) the level of protection the public experiences in many drinking water supplies across the nation. However, researchers [11] pointed out that the analysis was presented as an example and should not be used to endorse certain treatment schemes or to determine the risk at any particular site without site-specific analysis [7,9,11,33,[48][49][50][51][52][53].…”
Section: Figure 4 Relative Risk Shown On a Logarithmic Scale Posedmentioning
confidence: 99%
“…For developing country planners and decision makers, water will be the key resource and political consideration in the coming 50 years. In many of these nations and regions, how water is managed will make the difference between peace and conflict; poverty and prosperity [1][2][3][4][5][6][7][8][9]. Across the globe, 2 out of 10 people do not have access to safe drinking water, and in the US, many states face water shortages and droughts [10].…”
Section: Introductionmentioning
confidence: 99%